(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. L’intesa con l’Associazione Chiesa d’Inghilterra - 2. L’assenza di una legge generale nel periodo liberale - 3. La Conciliazione - 4. Il permanere dell’assenza di una legge comune - 5. Continuità e innovazione dopo il 1948 - 6. La mancata revisione della legge sui culti - 7. La polemica anticoncordataria - 8. Il progetto di una legge generale sulla libertà religiosa - 9. Un’unica legge per esigenze diverse - 10. La legge comune sul “fatto” religioso - 11. Il potenziale conflitto con le leggi di derivazione pattizia - 12. Uguaglianza e discriminazione - 13. Sulla possibile rilevanza dei diritti religiosi - 14. Sul rilievo di alcune minoranze - 15. Conclusioni. The law on accepted cults, the agreements and the need for a common regulation on the religious issue ABSTRACT: Taking the cue from the signing of the agreement with the association Chiesa d’Inghiterra, we note thelack of a common regulation not on religous freedom, which is protected by the rules of the Italian Constitution through directly effective regulations, and which could be invasive and inadequate, but of a common basic regulation on religion, such that in goes beyond the old law on accepted cults and equates, as far as possible, the condition of churches with an agreement with those that do not have one. The viewpoint of the bilaterally contracted law, inherited from and confirmed by the pre-Repubblican period, while meeting the needs of cults, is not able to ensure a certain uniformity of treatment for all denominations, i.e. it cannot be applied also to those cults that have not negotiated it, that do not want or cannot do so. What is lacking in a unilateral law of the State, which outlines the essential and common points, that is the basis and reference index for other laws, given that equality does not mean the same things and that differentiations are allowed, or rather imposed, as long as they are not arbitrary. Besides, there is the problem of religius instances referring to secular and profane aspects of the human person, which can be inserted into the formative process of the law, allowing for to norms, which in religiously motivated subjects receive a further compelling force. It is responsibility of a pluralist and secular State, aware and guarantor of its own values and indispensable rules, to supervise the process of synthesis of the different cultures.